Simulation of Continuous Bio-Reactor - Rudy Agustriyanto (Syiah Kuala University, 2015)
Dynamic study of bioprocess system plays a central role in bioprocess control. It is in fact on the basis of the time required for the development of the knowledge process that the total design, analysis and implementation of monitoring and control methods are carried out. Within the framework of bioprocesses, the most natural way to determine the models that will enable the characterization of the process dynamics is to consider the material balance of major components of the process. This article will present simulation results of continuous bio-reactor. The mathematical models for the bio-reactor based on the material balance had been derived (Riggs and Karim, 2006) and would be adopted in this study. Those model were solved and simulated using Matlab. It is found that the dynamic responses of the bio-reactor due to a step change in feedrate are first order.